2021
DOI: 10.1061/(asce)me.1943-5479.0000912
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Noncost Criteria Weighing in Best-Value Design–Build US Highway Projects

Abstract: United States highway agencies use best-value procurement with a fixed price to select design-builders. This method enables public agencies to choose the best proposer by assessing several factors in addition to price. Theoretically, considering cost and non-cost factors in the selection enhances the probability of selecting the proposer that provides the best value for each dollar spent. However, bidding results from the last 15 years show that 80% of best-value procurements are awarded the proposer with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Results from the Montecarlo simulation indicated that including a second non-cost criterion varies the probability of awarding the contract to the lowest bidder between 21.48% and 2.78%, depending on the weights given to the different criteria. This result suggests that the number of non-cost criteria has an influence on the likelihood of the lowest bidder being awarded the contract, as it does the ranges of the weights and scores ranges applied to those criteria, according to previous research [11].…”
Section: Does the Number Of Components In The Equation Impact The Pro...supporting
confidence: 57%
See 3 more Smart Citations
“…Results from the Montecarlo simulation indicated that including a second non-cost criterion varies the probability of awarding the contract to the lowest bidder between 21.48% and 2.78%, depending on the weights given to the different criteria. This result suggests that the number of non-cost criteria has an influence on the likelihood of the lowest bidder being awarded the contract, as it does the ranges of the weights and scores ranges applied to those criteria, according to previous research [11].…”
Section: Does the Number Of Components In The Equation Impact The Pro...supporting
confidence: 57%
“…Thus, a total of 406 observations were analyzed from the 128 projects collected. Scores from different procurements and criteria were harmonized to a scale ranging from zero to one, as was considered by Calahorra et al [11].…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Agency policy and legislation generally requires a low-bid approach in the traditional delivery method. Best-value procurement is preferred in design-build projects because it provides a balance between a low-bid procurement and qualification-based selection (Nguyen et al, 2018;Calahorra-Jimenez et al, 2020;Calahorra-Jimenez et al, 2021). In fact, many agencies require best-value selection for design-build projects because the price component corresponds to traditional low-bid selection of the builder and the qualification-based component corresponds to the traditional selection of the designer.…”
Section: Introductionmentioning
confidence: 99%